Women’s Agency, Discernment, and Choice in the English Convents in Exile, 1600–1800 - Kelly, James (The historical journal, 2025)
Studies of women religious during the early modern period have often focused on questions surrounding lack of choice, usually about whether they had been coerced to join a convent. This article argues that, in the case of the English convents formed in continental Europe after the Tridentine reforms, not only did most women opt to enter convents of their own free will, but that there was a further level of choice involved. Namely, women chose which convent they wished to enter, a decision process largely neglected by the existing historiography. It opens by considering the regulations the convents operated under as part of the Catholic Reformation, and argues that both the communities and individual women were involved in the decision process surrounding entry to convent life. The second section explores how women navigated any external influences, while the third section argues that spirituality was a key motivating factor for a woman choosing a community. In short, women were not just choosing to become nuns, but were exercising their own agency in deciding which convent to join. Committed candidates meant a strong community and, in the case of the English convents, it meant they could navigate the extra challenges of exile.